Multilevel personalization of explanations in recommender systems - Chalyi, S.; Leshchynsky, V.; Leshchynska, I. (My University, 2020)
The subject matter of the article is the process of building a personalized list of objects in recommendation systems. The goal is to develop a generalized formal description of the multi-level presentation of explanations in recommendation systems to personalize these explanations, taking into account the features of the use of recommended subjects. Such a description provides a formal framework for constructing a multi-level model of explanation, taking into account the static and dynamic characteristics of the subject area. Tasks: structuring the multi-level presentation of explanations in recommendation systems taking into account differences in the possibilities of personalizing explanations using data and knowledge; development of a formal presentation of explanations at the levels of data, information, knowledge and metacognition, taking into account the relationships between these levels. The approaches used are: approaches to the construction of explanations based on the similarity of user interests and properties of user demand items. The following results are obtained. The levels of explanation description are structured taking into account knowledge about the context of consumer choice. A formal description of the multi-level presentation of explanations in recommendation systems is proposed. Предметом вивчення в статті є процеси побудови персоналізованого переліку предметів в рекомендаційних системах. Метою є розробка узагальненого формального опису багаторівневого представлення пояснень в рекомендаційних системах для персоналізації таких пояснень з урахуванням особливостей використання рекомендованих предметів. Даний опис задає формальні рамки для побудови багаторівневої моделі пояснення з урахуванням статичних та динамічних характеристик предметної області. Завдання: структуризація багаторівневого представлення пояснень у рекомендаційних системах з урахуванням відмінностей у можливостях персоналізації витлумачень за допомогою даних та знань; розробка формального представлення пояснень на рівнях даних, інформації, знань та мета-знань з урахуванням зв'язків між цими рівнями. Використовуваними підходами є: підходи до побудови пояснень на основі схожості інтересів користувачів та властивостей предметів користувацького попиту. Отримані наступні результати. Виконано структуризацію рівнів опису пояснення з урахуванням знань щодо контексту вибору споживача. Запропоновано формальний опис багаторівневого представлення пояснень у рекомендаційних системах.
Keywords: recommender systems; representation of knowledge; recommendations; formation of explanations; knowledge; meta-knowledge; temporal rules